Comparing the Application of The Islamic Law of Succession and Administration of Estates in Singapore with South Africa - Muneer Abduroaf (Obiter, 2020)
This article investigates how the Islamic law of succession and administration of estates is applied in Singapore and South Africa with regard to the “Islamic will”. This kind of will includes a provision where the testator or testatrix states that his or her estate must be distributed in terms of the Islamic law of succession. This requires an Islamic law expert or an Islamic organisation to draft an Islamic distribution certificate stating who the beneficiaries of the person are. The distribution certificate is drafted after the testator or testatrix has died. An Islamic distribution certificate within the Singaporean context is specifically compared with one in the South African context. This article looks at whether features found in the Singaporean model can be applied to the South African context. An overview of the Muslim population in Singapore and South Africa is presented by way of introduction. This is followed by an examination of the constitutional and international obligations of the two countries in light of their equality provisions, and a comparative analysis of the Islamic law of succession and administration of estates in the two countries. The focus areas looked at are liability claims, testate succession claims and intestate succession claims. A brief analysis of the findings and concluding remarks are made at the end of the article.